Pneumomediastinum secondary to an apparently trivial stab wound to the neck: the value of the Hamman's sign and thorough radiological investigation. Issue 3 (25th February 2005) - Enguidanos, L; Pfleiderer, A; Smith, W; Ramkumar, S
Abstract : Perforation of the pharynx and upper oesophagus after stab wounds to the neck is easily overlooked because of the relative lack of symptoms. A case is reported in which pneumomediastinum occurred after an apparently trivial neck wound.